Modelling the influence of peri-urban trees in the air quality of Madrid region (Spain). - Alonso, Rocío; Vivanco, Marta G; González-Fernández, Ignacio; Bermejo, Victoria; Palomino, Inmaculada; Garrido, Juan Luis; Elvira, Susana; Salvador, Pedro; Artíñano, Begoña (Environmental pollution (Barking, Essex : 1987), 2011)
Tropospheric ozone (O(3)) is considered one of the most important air pollutants affecting human health. The role of peri-urban vegetation in modifying O(3) concentrations has been analyzed in the Madrid region (Spain) using the V200603par-rc1 version of the CHIMERE air quality model. The 3.7 version of the MM5 meteorological model was used to provide meteorological input data to the CHIMERE. The emissions were derived from the EMEP database for 2003. Land use data and the stomatal conductance model included in CHIMERE were modified according to the latest information available for the study area. Two cases were considered for the period April-September 2003: (1) actual land use and (2) a fictitious scenario where El Pardo peri-urban forest was converted to bare-soil. The results show that El Pardo forest constitutes a sink of O(3) since removing this green area increased O(3) levels over the modified area and over down-wind surrounding areas.
Keywords: Air Pollutants; Air Pollutants: analysis; Air Pollutants: metabolism; air pollution; Air pollution removal; Air Pollution: statistics & numerical data; Air quality models; Chemical; Cities; Dry deposition; Environmental Monitoring; Environmental Monitoring: methods; Models; Ozone; Ozone: analysis; Ozone: metabolism; Spain; Trees; Trees: classification; Trees: metabolism; Trees: physiology; Urban forest

Trace metal fluxes in bulk deposition, throughfall and stemflow at two evergreen oak stands in NE Spain subject to different exposure to the industrial environment - Avila, Anna; Rodrigo, Anselm (Atmospheric Environment, 2004)
We compare here the bulkdeposition, throughfall and stemﬂow ﬂuxes of dissolved trace metals in two holm oak (Quercus ilex L.) forests in the Montseny Mountains (NE Spain) with the aim of: (1) applying different methods to distinguish between dry deposition and canopy leaching and (2) to add to the almost non-existing deposition measurements for dissolved Cu, Pb, Mn, V, Zn, Ni and Cd in two Spanish forests differentially exposed to the urban and industrial environment. No signiﬁcant differences in mean bulkdeposition concentrations or ﬂuxes were found between sites, indicating little differential effect of the urban/industrial environment on bulkprecipitation chemistry. At both sites, throughfall and stemﬂow ﬂuxes increased relative to bulkdeposition for all elements, except for Zn and Cd. The relative contribution of leaching and dry deposition was evaluated through: (1) the seasonal variability of throughfall, (2) regressions of element ﬂuxes on water ﬂux in net throughfall, (3) washing branches and metacrylate plates, and (4) the sequential washing of branches. Results indicated that leaching was the main enrichment process for Mn. For Ni, except the sequential washings, all other evidences also pointed to leaching. For Cu, Pb, Zn, Cd and V there was ample evidence for dry deposition. The fact that Zn and Cd had negative net throughfall ﬂuxes indicated that canopy uptake was greater than deposition (wet plus dry). Net throughfall ﬂuxes pointed to higher dry deposition onto the canopies in the more exposed site, but the occurrence of uptake impeached quantiﬁcation. Therefore, dry deposition was estimated from the recovered quantities from experimental washings of foliage, taken to represent the impaction of small particles onto the canopy. The foliage-wash ﬂuxes were, for Zn, Cu and Pb, respectively, 407, 25 and 16 g ha 1 yr 1 at the sheltered site and 423, 38 and 26 g ha 1 yr 1 at the exposed site. Deposition in bulkprecipitation (wet deposition+an unknown fraction of dry deposition mostly accounted by coarse particles settling gravitationally) was lower: 222, 6.3 and 6.5 g ha 1 yr 1 for Zn, Cu and Pb, respectively, averaged for the two sites
Keywords: Dry deposition; Leaching; Mediterranean forests; surrogate surfaces; throughfall; Trace metals

Trace metal fluxes in bulk deposition, throughfall and stemflow at two evergreen oak stands in NE Spain subject to different exposure to the industrial environment - Avila, Anna; Rodrigo, Anselm (Atmospheric Environment, 2004)
We compare here the bulkdeposition, throughfall and stemﬂow ﬂuxes of dissolved trace metals in two holm oak (Quercus ilex L.) forests in the Montseny Mountains (NE Spain) with the aim of: (1) applying different methods to distinguish between dry deposition and canopy leaching and (2) to add to the almost non-existing deposition measurements for dissolved Cu, Pb, Mn, V, Zn, Ni and Cd in two Spanish forests differentially exposed to the urban and industrial environment. No signiﬁcant differences in mean bulkdeposition concentrations or ﬂuxes were found between sites, indicating little differential effect of the urban/industrial environment on bulkprecipitation chemistry. At both sites, throughfall and stemﬂow ﬂuxes increased relative to bulkdeposition for all elements, except for Zn and Cd. The relative contribution of leaching and dry deposition was evaluated through: (1) the seasonal variability of throughfall, (2) regressions of element ﬂuxes on water ﬂux in net throughfall, (3) washing branches and metacrylate plates, and (4) the sequential washing of branches. Results indicated that leaching was the main enrichment process for Mn. For Ni, except the sequential washings, all other evidences also pointed to leaching. For Cu, Pb, Zn, Cd and V there was ample evidence for dry deposition. The fact that Zn and Cd had negative net throughfall ﬂuxes indicated that canopy uptake was greater than deposition (wet plus dry). Net throughfall ﬂuxes pointed to higher dry deposition onto the canopies in the more exposed site, but the occurrence of uptake impeached quantiﬁcation. Therefore, dry deposition was estimated from the recovered quantities from experimental washings of foliage, taken to represent the impaction of small particles onto the canopy. The foliage-wash ﬂuxes were, for Zn, Cu and Pb, respectively, 407, 25 and 16 g ha 1 yr 1 at the sheltered site and 423, 38 and 26 g ha 1 yr 1 at the exposed site. Deposition in bulkprecipitation (wet deposition+an unknown fraction of dry deposition mostly accounted by coarse particles settling gravitationally) was lower: 222, 6.3 and 6.5 g ha 1 yr 1 for Zn, Cu and Pb, respectively, averaged for the two sites
Keywords: Dry deposition; Leaching; Mediterranean forests; surrogate surfaces; throughfall; Trace metals

The chemistry of precipitation, throughfall and stemflow in two holm oak (Quercus ilex L.) forests under a contrasted pollution environment in NE Spain. - Rodrigo, a; Avila, A.; Roda, F. (The Science of the total environment, 2003)
Atmospheric deposition was studied through measurements of bulk deposition, throughfall and stemflow at two sites of contrasted exposure to pollution in the Montseny mountains (Northeastern Spain). To explore the contribution of local or distant sources at both sites, concentration data and precipitation amounts (log transformed) for both bulk deposition and net throughfall were fitted by linear regression. These models indicated the more important contribution of washout scavenging processes and dry deposition at the pollution exposed site. This is relevant in the context of Mediterranean holm oak forests: up to now, most of the studies have been conducted in protected remote sites and were little representative of the fluxes in forests close to industrial activity, traffic, agriculture and residential areas.
The following values have no corresponding Zotero field: accession-num: 12670768
Keywords: bulk deposition; Dry deposition; Holm oak forest; Leaching; N uptake; throughfall

The chemistry of precipitation, throughfall and stemflow in two holm oak (Quercus ilex L.) forests under a contrasted pollution environment in NE Spain. - Rodrigo, a; Avila, a; Rodà, F (The Science of the total environment, 2003)
Atmospheric deposition was studied through measurements of bulk deposition, throughfall and stemflow at two sites of contrasted exposure to pollution in the Montseny mountains (Northeastern Spain). To explore the contribution of local or distant sources at both sites, concentration data and precipitation amounts (log transformed) for both bulk deposition and net throughfall were fitted by linear regression. These models indicated the more important contribution of washout scavenging processes and dry deposition at the pollution exposed site. This is relevant in the context of Mediterranean holm oak forests: up to now, most of the studies have been conducted in protected remote sites and were little representative of the fluxes in forests close to industrial activity, traffic, agriculture and residential areas.
Keywords: bulk deposition; Dry deposition; Holm oak forest; Leaching; N uptake; throughfall

Nitrogen circulation in a Mediterranean holm oak forest, La Castanya, Montseny, northeastern Spain - Avila, Anna; Rodrigo, Anselm; Rodà, Ferran (Hydrology and Earth System …, 2002)
Bulk deposition, wet-only deposition, throughfall and dry deposition inferred from washing foliage and surrogate surfaces were used to describe inorganic N inputs to a forested catchment in the Montseny Mountains (La Castanya, Catalonia, Spain). Bulk inputs of inorganic N were moderate, with a mean of 5.7 kg N ha -1 yr -1 , ranging between 4 and 10 kg N ha -1 yr -1 for the period 1983 to 2000. Dry deposition fluxes estimated from washing branches added about 9 kg N ha -1 yr -1 to wet inputs and the total atmospheric deposition was estimated in 15 kg N ha -1 yr -1 . Despite this substantial input flux, nearly all the inorganic nitrogen was retained within the forest ecosystem: NH4 + and NO3 - concentrations decreased dramatically as water crossed the canopy and the soil profile. In the stream, at baseflow conditions, NH4 + and NO3 - concentrations were always below the analytical detection limit (< 2 µeq L -1 ). Only briefly during peak flows did NO3 - concentrations increase up to 100 µeq L -1 . Averaged over 10 years (1984-1994), the export of N at the catchment outlet was 0.05 kg N ha -1 yr -1 . This indicates a very tight N cycling allowing for an increase of N availability in these undisturbed forest ecosystems.
Keywords: ammonium; bulk deposition; Dry deposition; la castanya; montseny; nitrate; soil water; Spain; throughfall

Nitrogen circulation in a Mediterranean holm oak forest, La Castanya, Montseny, northeastern Spain - Avila, Anna; Rodrigo, Anselm; Rodà, Ferran (Hydrology and Earth System …, 2002)
Bulk deposition, wet-only deposition, throughfall and dry deposition inferred from washing foliage and surrogate surfaces were used to describe inorganic N inputs to a forested catchment in the Montseny Mountains (La Castanya, Catalonia, Spain). Bulk inputs of inorganic N were moderate, with a mean of 5.7 kg N ha -1 yr -1 , ranging between 4 and 10 kg N ha -1 yr -1 for the period 1983 to 2000. Dry deposition fluxes estimated from washing branches added about 9 kg N ha -1 yr -1 to wet inputs and the total atmospheric deposition was estimated in 15 kg N ha -1 yr -1 . Despite this substantial input flux, nearly all the inorganic nitrogen was retained within the forest ecosystem: NH4 + and NO3 - concentrations decreased dramatically as water crossed the canopy and the soil profile. In the stream, at baseflow conditions, NH4 + and NO3 - concentrations were always below the analytical detection limit (< 2 µeq L -1 ). Only briefly during peak flows did NO3 - concentrations increase up to 100 µeq L -1 . Averaged over 10 years (1984-1994), the export of N at the catchment outlet was 0.05 kg N ha -1 yr -1 . This indicates a very tight N cycling allowing for an increase of N availability in these undisturbed forest ecosystems.
Keywords: ammonium; bulk deposition; Dry deposition; la castanya; montseny; nitrate; soil water; Spain; throughfall

Aerodynamic characterisation of model tree canopies in a wind tunnel - Kinnersley, R P; Farrington-Smith, J G; Shaw, G; Minski, M J (Science of The Total Environment, 1994)
The aerodynamic characteristics of ‘model’ tree canopies within a wind tunnel are reported. Wind speed profiles above and within canopies comprising Norway spruce (Picea abies) and Holm oak (Quercus ilex) saplings were determined by hot wire and hot film anemometry at a free-stream air velocity subsequently used for experiments on the dry deposition of aerosol particles to both canopies. Friction velocities (U∗) of 128 and 104 cm s−1 were observed for Norway spruce and Holm oak, respectively. Vertical distributions of wind speed (U) and turbulence intensity (i) within the canopies were similar in form and magnitude to those reported in the literature for full-sized forest canopies, suggesting that the sapling canopies provide a realistic ‘model’ with which to investigate the process of dry deposition.
Keywords: Boundary Layer; Dry deposition; Forest canopy; Turbulence

AERODYNAMIC CHARACTERIZATION OF MODEL TREE CANOPIES IN A WIND-TUNNEL - Kinnersley, R P; FARRINGTONSMITH, J G; Shaw, G; Minski, M J (SCIENCE OF THE TOTAL ENVIRONMENT, 1994)
The aerodynamic characteristics of `model' tree canopies within a wind tunnel are reported. Wind speed profiles above and within canopies comprising Norway spruce (Picea abies) and Holm oak (Quercus ilex) saplings were determined by hot wire and hot film anemometry at a free-stream air velocity subsequently used for experiments on the dry deposition of aerosol particles to both canopies. Friction velocities (U{*}) of 128 and 104 cm s-1 were observed for Norway spruce and Holm oak, respectively. Vertical distributions of wind speed (U) and turbulence intensity (i) within the canopies were similar in form and magnitude to those reported in the literature for full-sized forest canopies, suggesting that the sapling canopies provide a realistic `model' with which to investigate the process of dry deposition.
Keywords: Boundary Layer; Dry deposition; Forest canopy; Turbulence